Online Marketing Communication Strategy To Increase The Customers In Seblak Bloom Purwodadi - Athoillah; Myra Heltyani (LPPM Universitas An Nuur, 2021)
Background: Marketing communication strategy is a plan that will be used by a company to conduct marketing and determine the company's goals and objectives. Marketing strategy is also used to carry out sales activities by using communication techniques that aim to provide information to the target audience so that the company's goals can be successful. The marketing communication strategy is designed to be effective and efficient with easy distribution of messages and minimal effort is spent on these marketing communication activities.Purpose: The purpose of this study is to examine more deeply about online marketing communication strategies to increase the number of customers at Seblak Bloom Purwodadi.Methods: This study uses a qualitative method which is carried out through observation and interviews with the object directly, namely the owner of Seblak Bloom Purwodadi. This method aims to obtain more complete information and be able to achieve a wider scope related to online marketing communication strategies at Seblak Bloom Purwodadi.Conclusion: From the results of observations and interviews conducted, it can be concluded that in maintaining business existence from seblak blooms, the owner creates business strategies by adopting digital technology which is said to be more effective and efficient, for example the use of applications with many users such as Facebook and Instagram which are often operated by the millennial generation.Suggestion: There are still many limitations in this research and need to be developed again for future research agendas. The scope of this research is still small and in a less broad scope because it is only driven by one informant, so that future research can be developed through the addition of variables and the number of objects to be studied.